Factorial Invariance of the Satisfaction with Life Scale (SWLS) in Mexican and Colombian University Students - Ignacio Norambuena-Paredes; Karina Polanco-Levicán; Julio Tereucán-Angulo; José Sepúlveda-Maldonado; José Luis Gálvez-Nieto; Cristina Tavera-Cuellar; Selene Pérez-Ramírez; Crisóforo Álvarez-Violante; Roque López-Tarango (Behavioral Sciences)
This study aimed to evaluate the psychometric equivalence of the Satisfaction with Life Scale (SWLS) in university students from Mexico and Colombia. A non-probabilistic convenience sampling was used in five public and private universities in both countries, with a sample of 861 university students (40% men and 60% women), whose average age was 20.55 years (SD = 2.72). A six-point version of the SWLS was employed. Through confirmatory factor analysis, a unidimensional structure of the SWLS was identified in both samples, with adequate fit indices in both countries. Additionally, the factorial invariance analysis confirmed the metric and configural equivalence of the model, indicating that the factorial structure and factor loadings are comparable between both populations. The results support the use of the SWLS to assess life satisfaction in the context of university education in Mexico and Colombia.